Optical properties and structure of As-Ge-Se thin films - Tolmachov, I.D.; Stronski, A.V.; Vlcek, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Thin chalcogenide films with compositions As₁₀Ge₂₂.₅Se₆₇.₅ and As₁₂Ge₃₃Se₅₅
have been investigated. Optical constants and thicknesses of these films were obtained
from transmission spectra. Structure of initial bulk glasses and films were investigated by
Raman spectroscopy. Both films are estimated to have high values of the nonlinear
refractive index.